Innovative Regenerative Technologies for Enhancing Resilience in Salinity‐Stressed Rice Fields Along the Indonesian Coast: Promoting Net‐Zero Farming Practices to Adapt to Climate Change - Irwandhi Irwandhi; Fiqriah Hanum Khumairah; Emma Trinurani Sofyan; Ukit Ukit; Rievansyah Eka Satria; Annisya Salsabilla; Muhamad Sopyan Sauri; Tualar Simarmata (Journal of Sustainable Agriculture and Environment)
ABSTRACT Rice cultivation significantly contributes to greenhouse gas (GHG) emissions, particularly methane released from flooded paddy fields, exacerbating climate change. At the same time, rice farming is highly sensitive to climate conditions, with climate change introducing various abiotic stresses, notably salinity stress. This is especially critical in coastal regions like Indonesia, where rising sea levels and land degradation worsen the salinity challenge. This review systematically examines salinity stress in coastal rice cultivation, the impact of climate change on salinity dynamics and crop performance, and the potential of innovative regenerative technologies to enhance resilience and create low‐salinity, net‐zero agricultural systems. We conducted a systematic literature review following PRISMA guidelines, supplemented by a bibliometric analysis using Scopus, employing keywords such as “salinity stress”, “rice”, “agriculture”, “climate change” and “regenerative”. From an initial 2,191 articles, 18 were deemed eligible for further analysis. Findings indicate that increased soil salinity adversely affects rice production, yet innovative strategies such as rhizomicrobiome engineering, salt‐tolerant rice varieties, regenerative soil amendments, irrigation management, agricultural practices offer viable solutions to mitigate salinity stress. Furthermore, adopting net‐zero farming practices can help achieve carbon neutrality in agriculture while significantly reducing GHG emissions. This review highlights the need for a collaborative approach among scientists, farmers, and policymakers to scale these innovations, ensuring their implementation not only in Indonesia but also in other regions facing similar challenges, thereby promoting food security and environmental sustainability in the face of climate change.